Association between maternal age, nutritional status, and toddler stunting - Meidiantri; Palimbo, Adriana; Salmarini, Desilestia Dwi; Salmarini, Zulliati; Jannah, Raudhatul (Health Sciences International Journal, 2025)
Background:  Stunting remains a major public health issue in Indonesia, with Central Kalimantan reporting prevalence rates higher than the national. Maternal risk factors—particularly age at pregnancy and nutritional status—are known contributors to stunting, yet their direct influence in regional contexts remains underexplored. Objective:   This study aimed to analyze the association between maternal age and maternal nutritional status during pregnancy with the incidence of stunting among toddlers. Methods:   A retrospective cross-sectional analytic study was conducted from August to October 2024, involving 83 toddlers selected via purposive sampling from a population of 481 registered at the health center. Data were collected from maternal and child health handbooks (KIA), focusing on maternal age at pregnancy, mid-upper arm circumference (MUAC), and toddler height-for-age z-scores. Chi-square tests were performed to assess associations between maternal variables and stunting, with a significance threshold of p < 0.05. Results:   The majority of mothers were aged 20–35 years (74.7%) and had normal nutritional status (72.3%). The prevalence of toddler stunting was 26.5%. A statistically significant association was found between maternal chronic energy deficiency (CED; MUAC < 23.5 cm) and toddler stunting (p < 0.001), with 87% of children born to CED mothers being stunted. However, maternal age showed no significant correlation with stunting (p = 0.970). Conclusion: Maternal nutritional status during pregnancy, specifically CED, is significantly associated with toddler stunting, underscoring the need for targeted maternal nutrition interventions. Maternal age alone was not a significant factor in this cohort, suggesting other confounders may influence child growth.